Basic mechanics of DNA methylation and the unique landscape of the DNA methylome in metal-induced carcinogenesis. (July 2013) - Brocato, Jason; Costa, Max
Abstract DNA methylation plays an intricate role in the regulation of gene expression and events that compromise the integrity of the methylome may potentially contribute to disease development. DNA methylation is a reversible and regulatory modification that elicits a cascade of events leading to chromatin condensation and gene silencing. In general, normal cells are characterized by gene-specific hypomethylation and global hypermethylation, while cancer cells portray a reverse profile to this norm. The unique methylome displayed in cancer cells is induced after exposure to carcinogenic metals such as nickel, arsenic, cadmium, and chromium (VI). These metals alter the DNA methylation profile by provoking both hyper- and hypo-methylation events. The metal-stimulated deviations to the methylome are possible mechanisms for metal-induced carcinogenesis and may provide potential biomarkers for cancer detection. Development of therapies based on the cancer methylome requires further research including human studies that supply results with larger impact and higher human relevance.